2007
DOI: 10.1016/j.ejogrb.2006.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Compliance to clinical guidelines for early-stage epithelial ovarian cancer in relation to patient outcome

Abstract: Objectives: To assess compliance to current surgical staging and adjuvant treatment guidelines for patients with early-stage epithelial ovarian carcinoma and its impact on overall survival. Methods: Patients diagnosed between 1991 and 1997 with early-stage ovarian cancer were recruited from the Regional Cancer Registry of the central region in the Netherlands. Demographic data, tumour characteristics, surgical findings and therapeutic data were abstracted from medical records. Patients were classified into opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…Theoretically, this could lead to more advantageous effects of adjuvant chemotherapy in the ACTION and ICON1 trials, which cannot be demonstrated in our study, because of its retrospective nature. Sijmons et al [11] and Dinkelspiel et al [12] reported no significant benefits of adjuvant chemotherapy with respect to survival rates, which is in accordance with our data [11,12]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Theoretically, this could lead to more advantageous effects of adjuvant chemotherapy in the ACTION and ICON1 trials, which cannot be demonstrated in our study, because of its retrospective nature. Sijmons et al [11] and Dinkelspiel et al [12] reported no significant benefits of adjuvant chemotherapy with respect to survival rates, which is in accordance with our data [11,12]. …”
Section: Discussionsupporting
confidence: 93%
“…However, both early- and advanced-stage ovarian cancer patients were included in this analysis. In 2006, Sijmons et al [11] published a retrospective cohort study analyzing adherence to guidelines in early-stage EOC patients in the Netherlands. In their study, it was shown that 10% of optimally staged patients and 7% of nonoptimally staged patients received chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, data have also become available from studies in oncologic contexts, both related and not related to the details of radiotherapeutic management, that confirm and reinforce the role of protocol adherence for optimal survival (23, 2527). …”
Section: Discussionmentioning
confidence: 87%
“…Of the 11 studies grouped under guideline adherence and deviation, 8 utilised the NCCN ovarian cancer guidelines as the comparator guideline, with 3 using their own local or national guidelines [3,[17][18][19][20][21][22][23][24][25][26]. These studies collectively indicated variation in adherence to guidelines for both surgical staging and receipt of chemotherapy.…”
Section: Guideline Adherence and Deviationmentioning
confidence: 99%